Distinctness and Endemicity of the Vegetative Cover of Altai Transboundary Mountain Region and its Conservation as a Part of the Strategy for Altai Sustainable Development - GARMS, Evgenia O.; SUKHOVA, Maria G.; ZHURAVLEVA, Olga V.; KARANIN, Andrey V.; Minaev, Alexander I. (Journal of Environmental Management and Tourism, 2017)
The Altai transboundary mountainous region is a significant part of the Altai-Sayan ecoregion, namely one of almost 240 regions of the world, in which more than 80% of the world's biodiversity is preserved. Therefore, the relevance of the work lies in its description, which can help in future to protect the biodiversity of the region. The purpose of the article is to study and describe the originality of the territory’s floral zoning. The works of Ogureyeva, Kamelin, Yegorina, materials from the Green Book of Siberia, various atlases and other information were used to describe the vegetation of the natural and recreational areas. The leading method, which allowed to thoroughly study the research issue, was the evaluation of the bioclimatic characteristics. Since the normal development of the territory’s vegetation depends on climatic factors. A detailed characteristics of the vegetation cover of Tigireksky, Bashchelaksky, Koksuisko-Korgonsky natural and recreational areas was carried out in the work. It has been established that the inventory and preservation of the natural ecosystems’ diversity helps to preserve a stable state of natural potential. Also, we conducted an analysis of national parks. As a result of the research, it was revealed that many vegetation species are entered in the Green Book of Siberia